Examining the role of personality traits, digital technology skills and competency on the effectiveness of fraud risk assessment among external auditors - Nurul Izzaty Mat Ridzuan; Jamaliah Said; Fazlida Mohd Razali; Dewi Izzwi Abdul Manan; Norhayati Sulaiman (Journal of Risk and Financial Management, 2022)
In accordance with ISA 240, it is the responsibility of external auditors to obtain reasonable assurance that financial statements are free from material misstatement, whether caused by fraud or error. Recently, the auditing profession in Malaysia has been significantly challenged by the explosion of fraud cases and by auditors' failure to determine the "true and fair view" of the financial statement. This incident has tarnished the reputation of the audit profession. The effectiveness of the external auditor function, especially when related to fraud risk assessment, is commonly called into question. Hence, this study aims to assess individual factors (personality traits, digital technology skills, and competency) that may contribute to the effectiveness of fraud risk assessment among external auditors. A total of 455 questionnaires were distributed to external auditors, and a total of 150 (32.96%) responses were received. Data were thoroughly analyzed using Smart-PLS 4.0. This study found that digital technology skills contribute to the effectiveness of fraud risk assessment, whereas personality traits and competency do not. The findings implied that an effective technique of fraud risk assessment among external auditors requires digital technology skills. This study contributes to the literature by confirming the critical role of digital technology skills in enhancing the effectiveness of fraud risk assessments.
Keywords: M4; O3; 650; fraud risk assessment; competency; personality traits; digital technology skills